IMPLEMENTASI OPERASIONAL ZAKAT INFAK DAN SEDEKAH DALAM MEWUJUDKAN KESEJAHTERAAN PERSPEKTIF EKONOMI ISLAM (Studi di Koperasi Simpan Pinjam Pembiayaan Syariah Baitul Maal Wat Tamwil Fajar Metro) - Darajat, Ulfah Alfiyah; Suharto, Suharto; Bahrudin, Moh. (Universitas Islam Negeri Raden Intan Lampung, 2021)
Islam guarantees a distribution of income that contains human values. For example, the guidance to distribute wealth through zakat, infaq, shadaqah (ZIS) and others in order to maintain harmony in social life. ZIS can be used to open work opportunities in the form of capital assistance, educational assistance, health facility assistance and so on, so that later will be more productive. This paper will specifically examine comprehensively the operation of ZIS and its implementation in realizing prosperity in the perspective of Islamic economics at KSPPS BMT Fajar Metro. This is a field research with a qualitative descriptive approach. The data consists of primary and secondary sources which are then collected by interview, observation and documentation methods. Data analysis through data reduction, data display and drawing conclusions and verification. The interesting findings of this study are, first, that ZIS management operations are divided into two, on the collection of funds and their distribution. Sources of funds for the collection of ZIS funds and other religious social funds. Second, the operational implementation of ZIS in realizing the welfare of society from an Islamic economic perspective can be seen from two aspects, namely according to the Qur'an and hadith as well as Islamic economists.